2010
DOI: 10.1007/s11914-010-0026-z
|View full text |Cite
|
Sign up to set email alerts
|

Depression, Selective Serotonin Reuptake Inhibitors, and Osteoporosis

Abstract: An increasing number of studies suggest an association between depression and osteoporosis. In a mouse model, depression induces bone loss, mediated by brain-to-bone sympathetic signaling. Depression and bone antianabolic sympathetic tone are alleviated by increasing central serotonin (5-hydroxytryptamine, 5-HT) levels. However, selective serotonin reuptake inhibitors (SSRIs), the first-line antidepressants, increase extracellular 5-HT levels but have deleterious skeletal effects. The skeletal serotonergic sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 48 publications
1
23
0
2
Order By: Relevance
“…This finding is consistent with results from studies involving patients with mental health disorders 22–28. The sustained higher risk among SSRI users is also consistent with the biological hypothesis that fractures associated with SSRI use can be at least partially attributed to antidepressant-related modulation of bone homeostasis in favour of osteoclastic activity, which may result in lower bone mineral density and higher risks of fractures 29. HRs were significantly different between cohorts only after the second year when we modelled risk without including lag and induction periods, suggesting as well that SSRIs may need several months to produce clinically meaningful cumulative effects on bone mineral density.…”
Section: Discussionsupporting
confidence: 81%
“…This finding is consistent with results from studies involving patients with mental health disorders 22–28. The sustained higher risk among SSRI users is also consistent with the biological hypothesis that fractures associated with SSRI use can be at least partially attributed to antidepressant-related modulation of bone homeostasis in favour of osteoclastic activity, which may result in lower bone mineral density and higher risks of fractures 29. HRs were significantly different between cohorts only after the second year when we modelled risk without including lag and induction periods, suggesting as well that SSRIs may need several months to produce clinically meaningful cumulative effects on bone mineral density.…”
Section: Discussionsupporting
confidence: 81%
“…Previous reviews have summarized the association between SSRIs and fracture and have tried to address the inconsistent findings regarding this association [22][23][24][25][26]. However, these reviews have neither provided an overall estimation of the effect of SSRIs on fracture nor systematically reviewed the subgroups of study design, study location, sex, and controlled confounders.…”
Section: Discussionmentioning
confidence: 99%
“…and A.F.B.) independently by examining reference lists from the original studies [7-15, 19-21, 29] and review articles [22][23][24][25][26] obtained during the electronic search.…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the association between chronic psychological stress and osteoporosis has been the subject of a growing body of research. The published literature, especially recent animal and human studies, showed that chronic psychological stress is a risk factor for developing osteoporosis [11][12][13][14][15]. In the present review, we aim to provide the current understanding of the relationship between chronic psychological stress and osteoporosis.…”
Section: Chronic Psychological Stress As a Risk Factor Of Osteoporosismentioning
confidence: 99%